Analisis Strategi Pemasaran dalam Meningkatkan Pendapatan Usaha Peternakan Ayam Petelur Ibu Anis di Nagari Guguak Kabupaten Padang Pariaman - Febrian, Indah; Rais, Muhammad (ARZUSIN, 2026)
Marketing strategies play an important role in increasing the income of laying hen farming businesses, especially small-scale family-managed businesses in rural areas. Although this topic has been examined in various previous studies, research specifically discussing marketing strategies for small-scale family-based laying hen farming businesses remains limited. This study aims to analyze marketing strategies in increasing the income of the laying hen farming business owned by Mrs. Anis in Nagari Guguak, Padang Pariaman Regency. This study used a qualitative approach with a case study design. The research participants consisted of the business owner, customers, and relevant stakeholders selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the Miles, Huberman, and Saldaña model through the stages of data reduction, data display, and conclusion drawing. The results showed that the marketing strategies implemented were still simple and conventional, involving direct marketing, communication through WhatsApp, and the strengthening of social relationships with regular customers. The supporting factors for marketing included good egg quality, customer loyalty, and trust-based relationships with consumers. Meanwhile, the inhibiting factors included limited business capital, suboptimal use of digital media, fluctuations in animal feed prices, and limited egg production. These findings contribute to the development of studies on marketing strategies and relationship marketing in the context of MSME-based laying hen farming businesses. The conclusion of this study affirms that strengthening digital marketing strategies, improving service quality, and maintaining customer relationships play an important role in supporting increased income for laying hen farming businesses.